Equilibrio del desarrollo agropecuario y la deforestación en la Amazonia Brasileña - Cattaneo, Andrea (International Food Policy Research Institute, 2004)
This report identifies the links among economic growth, poverty alleviation, and natural resource degradation in Brazil. It examines the effects of (1) a major devaluation of the Brazilian real (R$); (2) improvements of infrastructure in the Amazon to link it with the rest of Brazil and bordering countries; (3) modification of land tenure regimes in the Amazon agricultural frontier; (4) adoption of technological change in agriculture both inside and outside the Amazon; and (5) fiscal mechanisms to reduce deforestation. -- from Author's Abstract